2005
DOI: 10.1002/adsc.200505023
|View full text |Cite
|
Sign up to set email alerts
|

Study on an Aldol Reaction Catalyzed by Ti(IV)/Calix[n]arene Complexes

Abstract: Ti(IV)/calixarene complexes, formed in situ or previously prepared with standard procedures, can be conveniently used as efficient catalysts in the aldol reaction of Chans silyloxydiene with a range of aldehydes bearing either activating or deactivating groups, including aromatic, heteroaromatic and a,b-unsaturated ones. The structure of both calixarene ligand and aldehyde, as well as the reaction conditions, strongly influence the efficiency of the reaction. NMR experiments in conjunction with the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…Calixarene macrocycles [ 22 ] have found numerous applications in several areas of supramolecular chemistry, such as (bio)molecular recognition [ 23 ] and catalysis [ 24 ]. The widespread use of the calixarene derivatives is due to their convenient synthesis and to their chemical and conformational versatility [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calixarene macrocycles [ 22 ] have found numerous applications in several areas of supramolecular chemistry, such as (bio)molecular recognition [ 23 ] and catalysis [ 24 ]. The widespread use of the calixarene derivatives is due to their convenient synthesis and to their chemical and conformational versatility [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…For such materials containing early transition metals, 3 it has been recently shown that the metal and ether oxygens are in dative contact, which should facilitate induction of chiral information from pendant groups to the calixarene core and the bound metal. This approximate geometry has been explored somewhat in enantioselective catalysis, including homogeneous inorganic 4 and surfaceorganometallic catalysts, 5 and a Ti(IV)-calixarene catalyst with chiral groups at the lower rim, 6 as well as in epoxidation reaction intermediates such as chiral organic peroxide-bound Ti(IV) centers, which demonstrate enhanced reaction enantioselectivity upon anchoring in confined pores. 7,8 Here, we demonstrate the stereoselective synthesis of a new family of C 2 -symmetric calixarene ligands, which is known to be a desired symmetry for chiral catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Organocatalysts incorporating in the thiourea portion residues with a large van der Waals surface, able to display stabilizing secondary interactions with the substrate, were rarely investigated. Calixarene macrocycles , are of interest in supramolecular chemistry where they have shown amazing supramolecular properties. The aromatic cavity of the calixarene skeleton can be readily adorned with catalytically active groups such as urea or thiourea functions .…”
Section: Introductionmentioning
confidence: 99%